Parents knowledge, attitude, and practice on nutrition of child with severe acute malnutrition in Awi Zone public Hospitals, Northwest Ethiopia, 2023 - Yazew, Birhaneslasie Gebeyehu; Birhanu Yohanes, Yeneabat; Adane Endalew, Daniel; Bishaw Aynalem, Zewdu (Frontiers in Nutrition, 2025)
BackgroundIncorrect or insufficient child nutrition predisposing for different disease and crisis. Even it is stated at different countries, there are no studies in Ethiopia specifically in the Amara Region Awi Zone public hospitals, Northwest of Ethiopia to investigate parental nutritional awareness in childhood.ObjectivesTo investigate parental nutritional knowledge, attitude, and practice in childhood in Awi Zone public Hospitals, Northwest Ethiopia.MethodsA cross-sectional study design with a purposive convenience sampling method was done among 297 participants. Parents of children with severe acute malnutrition were invited to complete adapted questionnaires. Details of parents’ nutritional awareness (knowledge, practice, and attitude) were assessed in face-to-face structured health interviews with the data collectors. The collected data were checked, coded, and entered into Epi-info version 7 and exported to SPSS version 23 for further analysis. Descriptive statistics was applied.ResultsA total of 297 parents were involved with the mean age 29.66 ± 6.27 years. About 93% of parents were heard about their child’s nutrition and 66.6% resided in rural. Overall parent’s good knowledge, favorable attitude, and poor practice toward child nutrition were 50.8%, 21.2%, and 89.6%, respectively. Health institution delivery, 1.61 and 4.39 times were associated with Knowledge and attitude, respectively and good practice 2.42 times associated with Knowledge. Children with comorbidities were 4.7 and 2.32 time associated with parents’ attitude and practice, respectively.ConclusionParental awareness toward child nutrition is considered a significant target for public health interventions. Delivery site, presence of comorbidities, and practice were the significant factors associated with parents’ awareness. The majority of parents were aware of the positive impact of child nutrition on overall wellbeing. The State of Awi Zone, Northwest Ethiopia, would be cost-effective to train and professionally develop the Awi Zone public Hospitals and primary healthcare workers to be more experts in tackling parents’ nutritional awareness by providing family counseling.